Cytoskeleton Aberrations in Alkaptonuric Chondrocytes. Issue 7 (31st January 2017) - Geminiani, Michela; Gambassi, Silvia; Millucci, Lia; Lupetti, Pietro; Collodel, Giulia; Mazzi, Lucia; Frediani, Bruno; Braconi, Daniela; Marzocchi, Barbara; Laschi, Marcella; Bernardini, Giulia; Santucci, Annalisa
Abstract : Alkaptonuria (AKU) is an ultra‐rare autosomal genetic disorder caused by a defect in the activity of the enzyme homogentisate 1, 2‐dioxygenase (HGD) that leads to the accumulation of homogentisic acid (HGA) and its oxidized product, benzoquinone acetic acid (BQA), in the connective tissues causing a pigmentation called "ochronosis." The consequent progressive formation of ochronotic aggregates generate a severe condition of oxidative stress and inflammation in all the affected areas. Experimental evidences have also proved the presence of serum amyloid A (SAA) in several AKU tissues and it allowed classifying AKU as a secondary amyloidosis. Although AKU is a multisystemic disease, the most affected system is the osteoarticular one and articular cartilage is the most damaged tissue. In this work, we have analyzed for the first time the cytoskeleton of AKU chondrocytes by means of immunofluorescence staining. We have shown the presence of SAA within AKU chondrocytes and finally we have demonstrated the co‐localization of SAA with three cytoskeletal proteins: actin, vimentin, and β‐tubulin. Furthermore, in order to observe the ultrastructural features of AKU chondrocytes we have performed TEM analysis, focusing on the Golgi apparatus structure and, to demonstrate that pigmented areas in AKU cartilage are correspondent to areas of oxidation, 4‐HNE presence has been evaluated by means of immunofluorescence. J. Cell. Physiol. 232: 1728–1738, 2017. © 2016 Wiley Periodicals, Inc. Abstract : The cytoskeleton of alkaptonuric chondrocytes is severely alterated. Serum amyloid A is demonstrated to be present within alkaptonuric chondrocytes and to co‐localize with the three main cytoskeletal proteins: actin, vimentin, and β‐tubulin. These findings lead to hypothesize a role of SAA in cytoskeleton alterations of alkaptonuric chondrocytes.